Impact of the Covid-19 Pandemic on the Situation and Financial Results of the Ekstraklasa Football Clubs - Wyszyński, Artur (Olsztyn Economic Journal, 2023)
The objective of this study is to evaluate and compare the financial situation and results of 12 joint-stock companies running football clubs in the Polish Ekstraklasa during two periods of their activity. The first period was during the COVID-19 pandemic in Poland, and the second period was before the pandemic. The pandemic period covered two years (2020 and 2021), and the pre-pandemic period was 2019. The description of the financial situation was based on an evaluation of net income from sales, net financial results and equity, as well as liquidity ratios and debt. Deviations in the form of absolute differences were calculated to compare the two study periods, where the pre-pandemic ratios for 2019 were subtracted from the financial ratios for the COVID-10 pandemic period (2020 and 2021). The study shows that the financial situation during the two periods varied, and it cannot be clearly stated that the financial situation deteriorated during the pandemic. Despite lower revenue from the matchday, which was caused by reduced numbers of fans at stadiums, higher net income was noted in most clubs during the pandemic. This was a consequence of higher revenues from broadcast rights and sponsoring and advertising activities. Higher-income and revenue from recapitalisation by share issuance, supplementing equity and shareholder loans ensured the clubs’ financial liquidity during the pandemic. The clubs also maintained their liquidity owing to the financial resources received from the Polish government as part of the Anti-Crisis Shield. The clubs’ financial situation regarding equity deteriorated during the pandemic, as it decreased in most clubs. This was caused by higher negative financial results than before the pandemic. High losses, especially among the clubs which reported negative results before the pandemic, resulted in a further increase in negative equity.